2019
DOI: 10.1262/jrd.2019-049
|View full text |Cite
|
Sign up to set email alerts
|

The effects of electroporation on viability and quality of <i>in vivo</i>-derived bovine blastocysts

Abstract: The introduction of exogenous molecules into embryos is required for analyses of molecular dynamics and specific gene functions during early embryonic development. Electroporation is an effective method to transport exogenous molecules into cells, but is rarely used in bovine embryos. First, we evaluated the viability of in vivo-derived bovine blastocysts after electroporation with fluorescein (FAM) labeled-oligonucleotides with varying pulse numbers (3, 5, 7, and 10), while keeping the pulse duration at 1 mse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Another study utilized in vivo-derived blastocysts and examined the quality of hatched blastocysts and blastocysts with their ZP still intact after electroporation. The authors concluded that the intact status of a blastocysts' ZP played a role in the quality of blastocysts as the diameter of the hatched blastocysts shrank significantly after electroporation indicating a loss of quality, whereas the diameter of ZP intact blastocysts did not change significantly after electroporation (Tanihara et al, 2019a). The result supports previous experiments in mice embryos that found the removal of the ZP to potentially hinder embryonic development (Bronson and McLaren, 1970;Modliński, 1970;Chen et al, 2016;Troder et al, 2018;Miao et al, 2019;Tanihara et al, 2019a).…”
Section: Pulsessupporting
confidence: 72%
See 1 more Smart Citation
“…Another study utilized in vivo-derived blastocysts and examined the quality of hatched blastocysts and blastocysts with their ZP still intact after electroporation. The authors concluded that the intact status of a blastocysts' ZP played a role in the quality of blastocysts as the diameter of the hatched blastocysts shrank significantly after electroporation indicating a loss of quality, whereas the diameter of ZP intact blastocysts did not change significantly after electroporation (Tanihara et al, 2019a). The result supports previous experiments in mice embryos that found the removal of the ZP to potentially hinder embryonic development (Bronson and McLaren, 1970;Modliński, 1970;Chen et al, 2016;Troder et al, 2018;Miao et al, 2019;Tanihara et al, 2019a).…”
Section: Pulsessupporting
confidence: 72%
“…The authors concluded that the intact status of a blastocysts' ZP played a role in the quality of blastocysts as the diameter of the hatched blastocysts shrank significantly after electroporation indicating a loss of quality, whereas the diameter of ZP intact blastocysts did not change significantly after electroporation (Tanihara et al, 2019a). The result supports previous experiments in mice embryos that found the removal of the ZP to potentially hinder embryonic development (Bronson and McLaren, 1970;Modliński, 1970;Chen et al, 2016;Troder et al, 2018;Miao et al, 2019;Tanihara et al, 2019a). Camargo et al (2020) reported efficient knockout of bovine OCT4 following electroporation at 17 hpi using six 15 V/mm poring pulses of 1.5 ms at 50 ms intervals and a 10% decay rate of successive pulses.…”
Section: Pulsesmentioning
confidence: 99%